A significant feature of microvessels in magnifying narrow-band imaging for diagnosis of early gastric cancer - Kanesaka, Takashi; Uedo, Noriya; Yao, Kenshi; Ezoe, Yasumasa; Doyama, Hisashi; Oda, Ichiro; Kaneko, Kazuhiro; Kawahara, Yoshiro; Yokoi, Chizu; Sugiura, Yasushi; Ishikawa, Hideki; Kato, Minoru; Takeuchi, Yoji; Muto, Manabu; Saito, Yutaka (Endoscopy International Open, 2015)
Background and study aims: Magnifying narrow-band imaging (NBI) is more useful than conventional endoscopy for diagnosing early gastric cancer (EGC). However, evaluation of irregular microvascular patterns is subjective and is often difficult, even with expert eyes. The aim of this study was to clarify the most important microvascular patterns in magnifying NBI for diagnosis of EGC.Patients and methods: This was a post-hoc analysis of a multicenter prospective trial among nine Japanese hospitals. A total of 1353 patients underwent screening with white-light endoscopy and 362 patients had small (≤ 10 mm) depressed lesions. They were randomly assigned to magnifying NBI or white-light endoscopy followed by magnifying NBI. During diagnosis, magnifying NBI images were recorded before biopsy. All magnifying NBI images were reviewed and evaluated for the association of four features of microvessels – that is, dilation, tortuosity, difference in caliber, and variation in shape – with cancer diagnosis. Results: Images of 343 lesions (40 cancerous and 303 benign depression lesions) were evaluable. The diagnostic performance (sensitivity/specificity) of each finding was: dilation, 25/90 %; tortuosity, 55/24 %; difference in caliber, 13 /99 %; and variation in shape, 70/95 %. Multivariate analysis identified only variation in shape as being statistically significantly associated with diagnosis of cancer (odds ratio 38.0, 95 % confidence interval: 16.1 – 95.7, P < 0.001). All findings showed moderate agreement (κ values): dilation, 0.44; tortuosity, 0.33; difference in caliber, 0.26; and variation in shape, 0.48.Conclusions: A variation in shape was the most significant feature of microvessels observed in magnifying NBI for diagnosis of small depressed-type EGC.Study registration: UMIN-CTR000001072